Residential child care and the psychodynamic approach; is it time to try again? - Charles Sharpe (Scottish Journal of Residential Child Care)
Therapeutic approaches to residential child care in the UK have been greatly influenced by the psychodynamic theories of D.W. Winnicott (1965), Klein (1998), Bowlby (1965) and Bion (1970), among others. The psychodynamic model of residential child care stresses the importance of understanding the emotional development of children and young people. It places particular significance on the anxieties and fears which arise for children when healthy emotional development is disrupted in early childhood. These theorists acknowledge a debt to the psychoanalytic theories of Sigmund Freud which he proffered as an explanation of human development and behaviour. Freud (1977) proposed that painful inner conflicts borne out of unresolved developmental issues during infancy, though repressed in the unconscious, struggle for expression in our conscious behaviour throughout our lives. These expressions coming as they do from the individual’s unresolved infantile inner conflicts were, according to Freud, manifested in behaviours or defences which were socially harmful to the individual. Research such as the work done by Berridge and Brodie (1998) indicates that the vast majority of children in residential care have had early childhood disruptions or traumas such as physical or sexual abuse. Hence it would appear that this group of children could be helped by the use of psychodynamic approaches. Yet recent reviews such as that by Maher (2003) seem to indicate that the influence of psychodynamic approaches on residential practice is on the wane.